The Impact of Predict-Observe-Explain Learning Model Assisted by Environmental Media on the Scientific Attitudes of Fifth Grade Elementary School Students - Sintarini, Ni Putu Ita; Suniasih, Ni Wayan (Universitas Pendidikan Ganesha, 2024)
When discussing, students are still not active. This can be seen through students' lack of courage to express their ideas and lack of curiosity about the lesson material. Based on this, this research aims to analyze the influence of the POE learning model assisted by environmental media on the science and science attitudes of class V students. This research uses a quasi-experimental research design with a non-equivalent control group research design. The population of this study was all 426 class V students. The sampling technique used was cluster random sampling which obtained 28 students from the VB class as the experimental class and 29 students from the VA class as the control class. Data collection methods and instruments use questionnaire sheets. Scientific attitude data obtained from the results of data collection were analyzed using descriptive statistical techniques and inferential statistical analysis using the polled variance t-test. The results of the hypothesis test show that H0 is rejected and H1 is accepted. Thus, it can be concluded that the POE learning model assisted by environmental media has an influence on the science and science attitudes of fifth grade elementary school students. The implication of this research is that it can be used as a basis for developing research related to the use of the POE learning model in science and science subjects in elementary schools.